Photoexcitation control of excitation relaxation in mixed-phase Ruddlesden-Popper hybrid organic-inorganic lead-iodide perovskites - Stadlbauer, Anna; Eyre, Lissa; Biewald, Alexander; Rauh, Felix; Heindl, Markus W.; Liu, Shangpu; Zerhoch, Jonathan; Feldmann, Sascha; Hartschuh, Achim; Deschler, Felix (Advanced optical materials, 2024)
The electronic states and exciton binding energies of layered Ruddlesden-Popper (RP) metal-halide perovskites can be tailored through changes of their chemical composition, yielding multi-phase systems with complex energy cascades. Ultrafast photoexcitation relaxation with transfer dynamics into domains of increasing layer number has been reported for these materials. Here, ultrafast optical spectroscopy is used to report an unexpected excitation energy dependence of photoexcitation relaxation dynamics in mixed-dimensional benzylammonium cesium lead iodide RP perovskite (BeA2CsPb2I7) thin films, which gives rise to spectrally broadband luminescence over the visible region. Using transient absorption and photoluminescence spectroscopy it is found that excitations, which are formed in the n = 2 RP-phase after photoexcitation with ≈0.2 electron volt excess energy, transfer to higher layer number RP-phases on unexpectedly slow timescales of tens of picoseconds. Further, it is observed that such excitations are initially optically passive. Notably, luminescence occurs under these conditions from multiple RP-phases with optical bandgaps across the visible range, yielding broadband luminescence. The results hold potential for realization of broadband white-light emitters and other light-emitting devices.
Vorab online veröffentlicht: 02. Oktober 2023
Gesehen am 07.11.2023